Political Communication Channel and The Phenomenon of Political Communicators in Indonesia - Hendra Alfani (Communication Sphere, 2015)
ABSTRACTCommunications is one of the most important human activity. Every time a humancommunication activities in various forms and models. Communication activity shows that thereis a life that is taking place in society, where it occurs in the life of the interaction. Interactionstake place and take place because someone deliver the message in the form of certain formsand accepted others into his target, so those messages influenced the attitudes and behaviourof the parties in question. From the picture it looks that the object of study think thatcommunication takes place in a social system, is an important human activity. This issue isbecoming increasingly important in the review of political communication. Politicalcommunication encompasses the whole of society. The study of political communication will notbe perfect when interpersonal communications do not obtain a place that is important in thestudy. Although it must be admitted that most of the textbooks that discuss politicalcommunication in the United States are more focused on the role of mass media in politicalcommunications. Political scientists assumed that political communications including the studyobject of political science because of the messages conveyed in the communication processhad political characteristics, namely with regard to power, politics, State, Government, channel,communicators and komunikan involved in it to act in the position of them as perpetrators ofpolitical activity. Political scientists assumed that political communication is a symptom that isalways there in every political system, as well as other social scientists who assume that socialcommunication is an integral part of the community.Keywords: Communication, Politics, Channels and Communicators